Sequence determination and homology modeling of lipase from Marinobacter sp. LB - Avila, Jhosep (2018)
Family I lipases are industrially recognized for their catalytic activities of esterification, interesterification and transesterification. In this study, Marinobacter sp. LB lipase isolated from Salinas de Pilluana, San Martín was characterized by in silico analysis. For this purpose, lip gene was amplified by conventional Polymerase Chain Reaction (PCR) and nucleotide sequence was analyzed in silico. The tertiary structure was elucidated using the 1EX9 lipase from Pseudomonas aeruginosa PAO1 as a template and molecular docking was executed with three substrates. The lip gene had 927 bp and mature protein, 284 amino acids. The lipase had a molecular weight of 29.99 kDa and pI of 8.89. Also typicall catalytic triad residues of family I lipases (Ser78, Asp229 and His251) were identified. In addition, eleven peripheral α-helixs and seven internal β-sheets were found. Binding pocket and its affinity for lipids were demonstrated by making molecular couplings with trioctanoin, tributyrin and triolein, with energies of -314.28, -248.11 and -215.44 kcal/mol, respectively; amino acids of interaction being Asn167, Lys106, Trp172, Thr164, Ala179. In conclusion, a 3D structure of Marinobacter sp. LB lipase was built using homologous modeling and validated based on the stereochemical quality and amino acids environment; while docking analysis with lipases substrates allowed to demonstrate the amino acids that participate in the binding pocket.